082 Experiences of remote consulting for neurologists and patients during the COVID-19 pandemic: a national survey. Issue 6 (27th May 2022) - Stavrou, Maria; Eva, Lioutas; Joanna, Lioutas; Davenport, Richard
Abstract : Remote consulting is an emerging model in managing chronic neurological conditions and has been widely implemented during the COVID-19 pandemic. The main objective of this national survey was to investigate the initial experiences of remote consulting for neurologists and patients with chronic neuro- logical conditions during the first COVID-19 phase. In collaboration with the Scottish Association of Neurological Sciences and the Neurological Alliance of Scotland, we conducted a survey of 62 neurologists and 201 patients between October-November 2020. The overall consensus amongst neurologists was that remote consulting is a way of delivering healthcare efficiently in carefully selected groups of patients. For practical and technical reasons, there was signifi- cantly greater preference for phone over video consultations. The prevailing opinion was that consider- able ongoing effort is required to adapt and align structures, processes and neurology specialty training to successfully embed this new model of care. The vast majority of patients perceived remote consultations as safe, effective and convenient, with 89% patients being satisfied with their remote consultation experience. Although traditional face-to-face consultations were the favoured way of interaction for 62% of patients, a significant proportion preferred that some of their future consultations were performed remotely. Although not a replacement for face-to-face consultations, this survey illustrates that remote consulting can serve as an acceptable adjunct to traditional face-to-face consultations for doctors and patients. More research is required to identify its safety and applicability. mstavrou@ed.ac.uk|NIHR Bursary 66